Investigation of the Leather Time Management of Football Players in Elazig Province During the Covid 19 Process - Sezer, Süreyya Yonca; Çelikel, Baha Engin (İbrahim ERDEMİR, 2021)
In this study, it is aimed to examine the leisure management of football players in Elazig in terms of some variables during the Covid 19 process. 99 football players participated in the study voluntarily. A questionnaire form in which demographic characteristics were questioned and Leisure Management Scale were applied to the participants. SPSS 22 package program was used in the analysis of the data. In the analyses, the t-test was used to determine the difference between marital status and leisure time training and leisure management, and the one-way Anova test was used to determine the difference between age, education status and income status and leisure management. Tukey test was used as post-hoc analysis to determine between which groups the differences were after the Anova test. The level of significance in the analyzes was determined as p<0.05. During the Covid 19 process, football players; While it was seen that there was a significant difference in the sub-dimensions of the leisure time management scale in terms of age, income status and leisure time training variables (p<0.05), there was no significant difference in the sub-dimensions in terms of the marital status and educational status variable (p>0.05). As a result, in our study, it was found that there was a difference in the leisure time management sub-dimension levels of the football players according to some variables and the leisure time management levels of the football players were high. When the time management of the football players was examined, it was found that they used the time well. It is thought that the participants should be encouraged to participate in activities in their spare time and to do individual sports during the covid 19 process.

Bu çalışmada Covid 19 sürecinde Elazığ ilindeki futbolcuların boş zaman yönetiminin bazı değişkenler açısından incelenmesi amaçlanmıştır. Çalışmaya gönüllü olarak 99 futbolcu katıldı. Katılımcılara demografik özelliklerin sorgulandığı anket formu ile Boş zaman Yönetim Ölçeği uygulandı. Verilerin analizinde SPSS 22 paket programı kullanıldı. Analizlerde, medeni durum ve boş zamanlarınızda antrenman yapma durumu ile boş zaman yönetimi arasındaki farkı belirleyebilmek için t-testi, yaş, eğitim durumu ve gelir durumu ile boş zaman yönetimi arasındaki farkı belirleyebilmek için tek yönlü Anova testi kullanıldı. Anova testi sonrasında farklılıkların hangi gruplar arasında olduğunu tespit etmek amacıyla post-hoc analizi olarak Tukey testi kullanıldı. Analizlerde anlamlılık düzeyi p<0,05 olarak belirlendi. Covid 19 sürecinde futbolcuların; yaş, gelir durumu ve boş zamanlarda antrenman yapma durumu değişkenleri açısından boş zaman yönetimi ölçeği alt boyutlar düzeylerinde anlamlı fark olduğu görülürken (p<0,05), medeni durum ve eğitim durumu değişkeni açısından alt boyutlarda anlamlı fark olmadığı görüldü (p>0,05). Sonuç olarak çalışmamızda futbolcuların, boş zaman yönetimi alt boyut düzeylerinde bazı değişkenlere göre farklılık görüldüğü ve futbolcuların boş zaman yönetim düzeylerinin yüksek olduğu bulunmuştur. Futbolcuların zaman yönetimleri incelendiğinde zamanı iyi değerlendirdikleri bulunmuştur. Katılımcıların boş zamanlarında aktivitelere katılımı ve covid 19 sürecinde bireysel spor yapmaları için teşvik edilmesi gerektiği düşünülmektedir.
Covid 19 Sürecinde Elazığ İlindeki Futbolcuların Boş Zaman Yönetimlerinin İncelenmesi
Keywords: Sports Medicine; Spor Hekimliği